2018
DOI: 10.1111/jai.13710
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis of antivirus‐related TRIM genes in Dabry’s sturgeon Acipenser dabryanus

Abstract: TRIM proteins are a group of highly conserved proteins that participate in a variety of biological processes in innate immunity. However, the roles of the Acipenseridae trim genes in the anti‐bacterial immune response remained uncertain. In the present study, the Dabry’s sturgeon (Acipenser dabryanus) TRIM2, TRIM8, and TRIM59 protein sequences were found to be similar to Chicken (Gallus gallus), with identities 92.8%, 89.1%, and 79.4%, respectively. Meanwhile, the TRIM23, TRIM37, and TRIM82 proteins shared 95.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Although in sharks, sturgeon and teleosts a more complex receptor system is suggested than in mammals (Secombes & Zou 2017;Luo et al 2018b), all signalling pathways, downstream of IFNRs (interferon receptors) appear to be evolutionarily conserved between all these groups (Langevin et al 2013). Regulators, such as IRFs (interferon regulating factors) and TRIM (tripartite motif-containing) proteins are also described for these taxa (Ozato et al 2008;Secombes & Zou 2017;Li et al 2017c;Li et al 2019).…”
Section: Cytokinesmentioning
confidence: 99%
“…Although in sharks, sturgeon and teleosts a more complex receptor system is suggested than in mammals (Secombes & Zou 2017;Luo et al 2018b), all signalling pathways, downstream of IFNRs (interferon receptors) appear to be evolutionarily conserved between all these groups (Langevin et al 2013). Regulators, such as IRFs (interferon regulating factors) and TRIM (tripartite motif-containing) proteins are also described for these taxa (Ozato et al 2008;Secombes & Zou 2017;Li et al 2017c;Li et al 2019).…”
Section: Cytokinesmentioning
confidence: 99%
“…The LcTRIM21 was predominantly expressed in muscle, followed by gill, head kidney, and blood. Some other TRIM genes like Dabry's Sturgeon Acipenser dabryanus TRIM71 (Chen et al 2021), TRIM8 genes (Li et al 2019), and Zebrafish TRIM54 (Boudinot et al 2011) also showed higher expression in muscle. Moreover, TRIM21 was reported to be expressed in most histogenetic lineages than limiting expression to leukocytes (Vaysburd et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, sturgeon farms have suffered high mortality rates due to various bacterial diseases, resulting in huge losses to sturgeon aquaculture and research (Luo et al., 2018; Meng et al., 2011; Zhang, Xu, Boscari, et al., 2018). Immune‐related proteins such as IFNs, IFN receptors, interleukin 16/17, trim, lysozymes, antimicrobial peptides, and Toll‐like receptors (TLRs) have been characterised (Han et al., 2018; Kai et al., 2019; Youshen Li et al., 2019; Luo et al., 2018; Xu et al., 2019; Zhang, Xu, Boscari, et al., 2018; Zhang, Xu, Du, et al., 2018). The interferon‐stimulating, Mx and Viperin genes have also been reported in A. dabryanus (Zhang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%